2011
DOI: 10.1007/s11606-011-1912-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Modalities in Diabetic Nephropathy: Standard and Emerging Approaches

Abstract: Diabetes mellitus is the leading cause of end stage renal disease and is responsible for more than 40% of all cases in the United States. Current therapy directed at delaying the progression of diabetic nephropathy includes intensive glycemic and optimal blood pressure control, proteinuria/albuminuria reduction, interruption of the renin-angiotensin-aldosterone system through the use of angiotensin converting enzyme inhibitors and angiotensin type-1 receptor blockers, along with dietary modification and choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 206 publications
0
40
0
Order By: Relevance
“…However, the role of optimizing control to retard, prevent or reverse DN remains controversial5, and the number of patients with DN that ultimately develop ESRD remains unacceptably high4. The treatment of DN is therefore still an unresolved issue posing a formidable challenge36.…”
mentioning
confidence: 99%
“…However, the role of optimizing control to retard, prevent or reverse DN remains controversial5, and the number of patients with DN that ultimately develop ESRD remains unacceptably high4. The treatment of DN is therefore still an unresolved issue posing a formidable challenge36.…”
mentioning
confidence: 99%
“…Diabetes is the most common factor underlying chronic kidney disease, accounting for nearly 50% of new cases [4]. Diabetic nephropathy occurs in both type 1 and type 2 diabetes, and is characterized by initial glomerular hyperfiltration, followed by thickening of the GBM, glomerular hypertrophy, and mesangial expansion, ultimately leading to proteinuria, renal fibrosis, and end-stage renal disease.…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…CKD is a serious global health problem with increasing prevalence in association with growing rates of obesity [2,3], diabetes [4], and cardiovascular disease [5]. Currently, dialysis and kidney transplantation remain the only viable treatments despite significant complications associated with both.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that about 20-30% patients of diabetes are prone to develop diabetic nephropathy usually 5 or more years after the onset of diabetes mellitus (Abdel-Rahman et al, 2012). Moreover, diabetic nephropathy is the most common single cause of end-stage renal disease (Molitch et al, 2004).…”
Section: Introductionmentioning
confidence: 99%